Agroforestry as a strategy for climate change adaptation and mitigation - Newaj, Ram; Chavan, Sangram; Prasad, Rajendra (Indian Journal of Agroforestry, 2020)
Agroforestry is addressing the issues of designing ecologically sound and economically appealing strategies for climate change adaptation and mitigation. Being an intensive, integrated, intentional and interactive, it helps in creating favorable conditions in terms of microclimate modification, biodiversity conservation, soil health improvement and shelter (windbreaks and shelterbelts). Agroforestry practices are a potential tool to alter the harsh environment to provide better conditions for crop, forage and livestock productions. The induced conditions could be critical in providing extra resiliency to shifting temperature and moisture regimes. Further, the carbon sequestration with varied benefits creates opportunities in trading carbon and reducing farmers’ vulnerability. This paper discusses different adaptation and mitigation options provided by multifunctional agroforestry systems against climate change.